Drop size-dependent chemical composition in clouds and fogs, volume I: chapters 1-11 - Moore, Katharine F., author; Collett, Jeffrey, advisor; Kreidenweis, Sonia, committee member; Pielke, Roger, committee member; Buchan, Roy, committee member (Colorado State University. Libraries, 2002)
Cloud drop composition varies as function of drop size. More sophisticated atmospheric chemistry models predict this and observations at many locations around the world by multiple techniques confirm this. This variation can influence the cloud processing of atmospheric species. Aqueous-phase reaction and atmospheric removal rates for scavenged species, among other processes, can be affected by drop size-dependent composition. Inferences to these processes drawn upon single bulk cloud composition measurements can be misleading according to observations obtained using cloud water collectors that separate drops into two or more sizeresolved fractions. Improved measurements of size-dependent drop composition are needed to further examine these and related issues.

Two active multi-stage cloud water collectors were developed for sampling super-cooled drops in mixed-phase clouds and warm cloud drops, respectively. Both use the principles of cascade inertial impaction to separate drops into three fractions (super-cooled drop collector) and five fractions (warm cloud drop collector). While calibration suggests there is more drop overlap between stages than desired, consistently different drop fractions are still collected.

FROSTY - the super-cooled drop collector - has been used successfully to obtain size-resolved drop composition information during two field campaigns in Colorado. While the data are limited, FROSTY's field performance appears to be reasonably consistent during individual cloud events, although not predictable based solely upon its collection efficiency curves. Additional factors must be considering in evaluating its performance in future campaigns. Nevertheless, the ability to obtain consistent size-resolved drop composition information from super-cooled clouds was not previously possible.

Field data indicate that the warm cloud collector - the CSU 5-Stage - is able to resolve variations in the drop size-dependent composition not discernible with the two-stage size-fractionating Caltech Active Strand Cloud water Collector (sf-CASCC). Field performance evaluations suggest that the 5-Stage and the sf-CASCC compare well to each other for the range of sampling conditions experienced. Both collectors' performances differ from measurements made by the Caltech Active Strand Cloud water Collector #2 (CASCC2) in some specific sampling conditions, but otherwise agreement between the three collectors is good. Where the sf-CASCC indicates little drop variation in an orographic cloud study at Whiteface Mtn., NY, the 5-Stage indicates up to a factor of two difference may exist between the maximum and minimum drop concentrations for the major inorganic ions (ammonium, nitrate and sulfate). The sf-CASCC data suggest that typically a factor of 3 - 5 difference exists between large and small drop species' concentrations in radiation fogs measured in Davis, CA. Concurrent 5-Stage samples suggest the actual variation may be up to at least a factor of 4 - 5 greater, and that the smallest drops (approximately < 11 μm in diameter) are principally responsible for the strong observed concentration gradients between sizes. While the data are limited, the 5-Stage's results are consistent for all of the sample sets obtained during both field campaigns. Data from the 5-Stage emphasize that cloud drop chemical composition cannot be considered separately from the sampled cloud's microphysics and dynamics. Interpreting the 5-Stage's results necessarily draws upon both.

During the Davis campaign, additional measurements were performed to investigate species removal from the atmosphere via drop deposition and gas/liquid partitioning in-fog. Although subject to confounding effects, these investigations benefited from the additional insight 5-Stage data provided into the processes occurring. In particular, 5-Stage data and between-fog aerosol measurements suggest that deposition of the largest fog drops resulted in the relative removal of coarse mode aerosol particles from the atmosphere. 5-Stage data and gas-phase measurements suggest the ammonia/ammonium system may not be at equilibrium and provide some information about the nitrous acid/nitrite system not otherwise available. The 5-Stage has the potential to be a valuable tool in investigating the effects of fog and fog processing on the fate of ambient species.
Keywords: geophysics; environmental science